Antibiotic Sensitivity Patterns of Bacteria Isolated from Urinary Tract Infections of Pregnant Women in Sabratha City - Ibtesam O. Amer,; Asmaa AL. Bin Kourah,; Karima A. Alhuwaij, (AlQalam Journal of Medical and Applied Sciences, 2024)
Urinary tract infections (UTIs) are among the most prevalent reproductive system infections in women of childbearing age worldwide. This study aimed to identify Escherichia coli (E. coli) as a potential causative agent of UTIs in pregnant women and to assess the effectiveness of various antibacterial agents on the clinical samples collected. Conducted in 2021 at Sabratha Teaching Hospital, the study included 60 urine samples from pregnant women with a history of fever, vaginal discharge, and other clinical symptoms. Routine bacterial diagnostics and culture techniques were employed to identify and characterize bacterial isolates. All cases were confirmed by specialists in obstetrics and gynecology. The study successfully isolated and identified 19 bacterial strains: 11 isolates (57.9%) were identified as Escherichia coli, 1 isolate (5.3%) as Staphylococcus species, and 7 isolates (36.8%) as Staphylococcus aureus. The findings revealed that Escherichia coli exhibited a high sensitivity to ciprofloxacin (79%) in vitro. In contrast, other antibiotics, including amoxicillin, Augmentin, and ampicillin, elicited varying degrees of resistance. Notably, Escherichia coli showed resistance to ampicillin and rosuvine, indicating an alarming increase in resistance to these commonly used antimicrobials. This resistance trend poses a significant public health concern, as it can lead to more virulent and treatment-resistant bacterial infections. The study underscores the importance of routine bacteriological culture and sensitivity testing in managing UTIs, particularly in pregnant women. Furthermore, ensuring adequate healthcare can help prevent UTIs and maintain overall health in this population. تُعد التهابات المسالك البولية من بين أكثر الالتهابات انتشارًا في نظام التكاثر لدى النساء في سن الإنجاب على مستوى العالم. هدف هذه الدراسة إلى تحديد الإشريكية القولونية كعامل محتمل للتسبب في التهابات المسالك البولية لدى النساء الحوامل، وتقييم فعالية مجموعة من العوامل المضادة للبكتيريا على العينات السريرية المجمعة. أجريت الدراسة في عام 2021 في مستشفى صبراتة التعليمي، وشملت 60 عينة بول من النساء الحوامل اللاتي يعانين من تاريخ حمى، إفرازات مهبلية، وأعراض سريرية أخرى. تم استخدام تقنيات التشخيص البكتيري الروتينية وزرع الثقافة لتحديد وتوصيف العزلات البكتيرية. تم تأكيد جميع الحالات بواسطة متخصصين في أمراض النساء والتوليد. نجحت الدراسة في عزل وتحديد 19 سلالة بكتيرية: 11 عزلة (57.9%) تم تحديدها كـ E. coli، 1 عزلة (5.3%) كـ Staphylococcus، و7 عزلات (36.8%) كـ Staphylococcus aureus. أظهرت النتائج أن E. coli كانت حساسة بشكل كبير للسيبروفلوكساسين (79%) في المختبر. بالمقابل، أظهرت المضادات الحيوية الأخرى مثل الأموكسيسيلين، والأوغمنتين، والأمبيسيلين درجات متفاوتة من المقاومة. وخصوصًا، أظهرت E. coli مقاومة للأمبيسيلين والروزوفين، مما يشير إلى زيادة مقلقة في المقاومة لهذه العوامل المضادة للبكتيريا المستخدمة بشكل شائع. يشكل هذا الاتجاه في المقاومة مصدر قلق كبير للصحة العامة، حيث يمكن أن يؤدي إلى بكتيريا أكثر شدة ومقاومة للعلاج. تشدد الدراسة على أهمية إجراء اختبار الزرع البكتيري وفحص الحساسية بانتظام في إدارة التهابات المسالك البولية، خاصة لدى النساء الحوامل. علاوة على ذلك، فإن توفير الرعاية الصحية المناسبة يمكن أن يساعد في الوقاية من التهابات المسالك البولية والحفاظ على الصحة العامة في هذه الفئة